Interspecific relationships in co‐occurring populations of social parasites and their host ants. (3rd April 2013) - Witek, Magdalena; Casacci, Luca Pietro; Barbero, Francesca; Patricelli, Dario; Sala, Marco; Bossi, Simone; Maffei, Massimo; Woyciechowski, Michal; Balletto, Emilio; Bonelli, Simona
<x xml:space="preserve">Abstract</x> Myrmica ant colonies host numerous insect species, including the larvae of Maculinea butterflies and Microdon myrmicae hoverflies. Little is known about the interspecific relationships among these social parasites and their host ants occurring in sympatric populations. We investigated communities of social parasites to assess the strategies allowing them to share the same pool of resources (i.e. Myrmica colonies). The present study was carried out at five sites inhabited by different social parasite communities, each comprising varying proportions of Maculinea teleius, Maculinea nausithous, Maculinea alcon, and Microdon myrmicae. We investigated their spatial distributions, host segregation, the degree of chemical similarity between social parasites and hosts, and temporal overlaps in colony resource exploitation. Spatial segregation among social parasites was found in two populations and it arises from microhabitat preferences and biological interactions. Local conditions can drive selection on one social parasite to use a Myrmica host species that is not exploited by other social parasites. Myrmica scabrinodis and Myrmica rubra nests infested by larvae of two social parasite species were found and the most common co‐occurrence was between Ma. teleius and Mi. myrmicae. The successful coexistence of these two species derives from their exploitation of the host colony resources at different times of the year. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 109, 699–709.